CMD411 - History of Animation and Motion Design / College of Creative Arts - UiTM, College of Creative Arts (Universiti Teknologi MARA (UiTM), 2023)
This course introduces the history and theories of animation and motion design, including the early approaches to motion, the origin of animation forms and the history of motion design. Students will precede the changes in animation and motion graphics over the past and the emergence of new technologies that have changed the conventional of animation and motion design.